2019
DOI: 10.1111/jcmm.14594
|View full text |Cite
|
Sign up to set email alerts
|

Sigma‐1 receptor protects against ferroptosis in hepatocellular carcinoma cells

Abstract: Sigma‐1 receptor (S1R) regulates reactive oxygen species (ROS) accumulation via nuclear factor erythroid 2‐related factor 2 (NRF2), which plays a vital role in ferroptosis. Sorafenib is a strong inducer of ferroptosis but not of apoptosis. However, the mechanism of sorafenib‐induced ferroptosis in hepatocellular carcinoma (HCC) remains unclear. In this study, we found for the first time that sorafenib induced most of S1Rs away from nucleus compared to control groups in Huh‐7 cells, and ferrostatin‐1 completely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(90 citation statements)
references
References 36 publications
2
75
0
Order By: Relevance
“…Because genes might either facilitate or suppress ferroptosis, the transcriptional changes of SOFs and DOFs in the CIFI-stratified subgroups were investigated. ATF4, CA9, EGLN1, ELAVL1, FTH1, GPX4, HELLS, ITGB8, NFE2L2, SLC7A11, SQSTM1, and VDAC2 are well-investigated SOFs ( Dixon et al, 2012 ; Sun et al, 2016b ; Chen et al, 2017 ; Jiang et al, 2017 ; Zhang et al, 2018 ; Bai et al, 2019 ; Li et al, 2019 ). It was found that, excluding GPX4, NFE2L2, and SQSTM1, the remaining SOFs were significantly up-regulated in the high-CIFI subgroup of the GSE14520 cohort ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because genes might either facilitate or suppress ferroptosis, the transcriptional changes of SOFs and DOFs in the CIFI-stratified subgroups were investigated. ATF4, CA9, EGLN1, ELAVL1, FTH1, GPX4, HELLS, ITGB8, NFE2L2, SLC7A11, SQSTM1, and VDAC2 are well-investigated SOFs ( Dixon et al, 2012 ; Sun et al, 2016b ; Chen et al, 2017 ; Jiang et al, 2017 ; Zhang et al, 2018 ; Bai et al, 2019 ; Li et al, 2019 ). It was found that, excluding GPX4, NFE2L2, and SQSTM1, the remaining SOFs were significantly up-regulated in the high-CIFI subgroup of the GSE14520 cohort ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, ferroptosis, a biological process in which immune therapy and sorafenib converge to exert an anti-tumor effect, might have a fundamental impact on the treatment response of HCC. The understanding of the occurrence and regulation of ferroptosis has increased considerably in recent decades; however, only a few studies have explored the ferroptosis-related genes (FRGs) and pathways in HCC ( Louandre et al, 2013 , 2015 ; Carlson et al, 2016 ; Houessinon et al, 2016 ; Sun et al, 2016b ; Bai et al, 2019 ; Qi et al, 2019 ; Feng et al, 2020 ; Kim et al, 2020 ). With the currently available FRGs and immune-related genes (IRGs), and the accumulative data deposited in public databases like The Cancer Genome Atlas (TCGA), it is hypothesized that a prognostic molecular classifier based on the immune response and ferroptosis status might help to identify subgroups of HCC patients with distinct ferroptosis-immune phenotypes and survival profiles.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Sigma 1 receptor (S1R) is abundantly expressed in hepatocytes. Inhibition of this receptor also promotes ferroptosis in HCC cells 38,39 . Furthermore, there are many negative regulators of ferroptosis in HCC, such as nuclear factor erythroid 2related factor 2 (NRF2), metallothionein-1G (MT-1G), CDGSH iron-sulfur domain 1 (CISD1) and P53.…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 97%
“…All these proteins are closely related to ferroptosis. 22 ATF4 is commonly expressed in human organs and can be activated in response to various stress signals including hypoxia, endoplasmic reticulum stress, amino acid deprivation, and oxidative stress. High expression of ATF4 is known to be related to the growth of malignant tumors.…”
Section: Discussionmentioning
confidence: 99%